Dorsal Root Entry Zone Lesioning: Systematic Review - Galafassi, Giovanna Zambo; Aguiar, Paulo Henrique Pires; Takahashi, André Akira; Pagura, Jorge Roberto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction Dorsal root entry zone (DREZ) leasioning (DREZ-otomy) is considered an effective treatment for chronic pain due to spinal cord injuries, brachial and lumbosacral plexus injuries, postherpetic neuralgia, spasticity, and other conditions. The objective of the technique is to cause a selective destruction of the afferent pain fibers located in the dorsal region of the spinal cord.Objective To identify and review the effectiveness and the main aspects related to DREZ-otomy, as well as the etiologies that can be treated with it.Methods The PubMed, MEDLINE and LILACS databases were used as bases for this systematic review, having the impact factor as the selection criteria. The 23 selected publications, totalizing 1,099 patients, were organized in a table for systematic analysis.Results Satisfactory pain control was observed in 70.1% of the cases, with the best results being found in patients with brachial/lumbosacral plexus injury (70.8%) and the worst, in patients with trigeminal pain (40% to 67%).Discussion Most of the published articles observed excellent results in the control of chronic pain, especially in cases of plexus injuries. Complications are rare, and can be minimized with the use of new technologies for intraoperative monitoring and imaging.Conclusion DREZ-otomy can be considered a great alternative for the treatment of chronic pain, especially in patients who do not tolerate the side effects of the medications used in the clinical management or have refractory pain.
Keywords: neuropathic pain; dorsal root entry zone; radiculopathy; spinal cord